1997
DOI: 10.1046/j.1365-313x.1997.12061261.x
|View full text |Cite
|
Sign up to set email alerts
|

Maturation and secretion of a serine proteinase is associated with events of late microsporogenesis

Abstract: An antiserum against meiotic proteins which bind to DNA cellulose was generated as a tool to assist the identification and purification of microsporogenesis-specific proteins. In immunoblotting experiments, this antiserum identified three meiotic proteins which are differentially expressed in anthers during microsporogenesis. One of these proteins was purified and characterized by biochemical and immunological techniques. This 82 kDa protein is synthesized as a preproprotein, acquires glycans as it moves throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 0 publications
2
64
0
Order By: Relevance
“…A number of stage-specific genes have been isolated and functionally characterized with respect to their role in reproductive biology in Arabidopsis and several other plant species (reviewed in Taylor et al 1997;Sanders et al 1999;reviewed in Ma 2005). However, the genome-wide information of these specific gene expression patterns in relation to their developmental stages is still very limited.…”
Section: Introductionmentioning
confidence: 99%
“…A number of stage-specific genes have been isolated and functionally characterized with respect to their role in reproductive biology in Arabidopsis and several other plant species (reviewed in Taylor et al 1997;Sanders et al 1999;reviewed in Ma 2005). However, the genome-wide information of these specific gene expression patterns in relation to their developmental stages is still very limited.…”
Section: Introductionmentioning
confidence: 99%
“…In situ hybridization revealed that ag12 genes are expressed in Frankia-infected cells of A. glutinosa nodules. While subtilisin-like proteases of the Kex2-family have been shown to play an important role in the secretory pathway in yeast and mammalia (Vierstra 1996), only a few examples of subtilisin-like proteases from higher plants have been published (Kobayashi et al 1994;Yamagata et al 1994;Ribeiro et al 1995;Tornero et al 1996;Taylor et al 1997). The plant subtilases identified seem to be involved in microsporogenesis, fruit ripening, the infection of nodule cells by Frankia, and pathogen response, respectively.…”
mentioning
confidence: 99%
“…The plant subtilases identified seem to be involved in microsporogenesis, fruit ripening, the infection of nodule cells by Frankia, and pathogen response, respectively. They contain N-terminal signal peptides, suggesting that they are secreted to the plant extracellular matrix where they are presumably involved in the processing of pericellular substrates (Yamagata et al 1994;Ribeiro et al 1995;Tornero et al 1996;Taylor et al 1997).…”
mentioning
confidence: 99%
“…Total protein was isolated from 100 mg of Stage 2 anthers (Koltunow et al 1990) of tobacco plants using NRD buffer {20 mM Tris (pH 8.6), 10% glycerol, 1% SDS} (Taylor et al 1997;DeGuzman and Riggs 2000). The isolated proteins were quantified using a method by Lowry et al (1951).…”
Section: Protein Isolation and Zymogram Analysismentioning
confidence: 99%
“…observed during pollen development (Taylor et al 1997), similarly in Lilium, the serine proteinase LIM9 is secreted into anther locules (Radlowski et al 1996). Recently a gene, OsSIZ1, a small ubiquitin-related modifier (SUMO) E3 ligase that helps in anchoring SUMO to protein substrates for modifications has been shown to be developmentally regulated in rice reproductive tissues (Wang et al 2010).…”
mentioning
confidence: 97%